2009
DOI: 10.1186/1471-230x-9-55
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between TP53gene deletion, protein expression and chromosome 17 aneusomy in gastric adenocarcinoma

Abstract: BackgroundThis study evaluates the existence of numerical alterations of chromosome 17 and TP53 gene deletion in gastric adenocarcinoma. The p53 protein expression was also evaluated, as well as, possible associations with clinicopathological characteristics.MethodsDual-color fluorescence in situ hybridization and immunostaining were performed in twenty gastric cancer samples of individuals from Northern Brazil.ResultsDeletion of TP53 was found in all samples. TP53 was inactivated mainly by single allelic dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
(33 reference statements)
5
18
0
Order By: Relevance
“…This finding corroborates our previous study using dual-color FISH for chr17/ TP53 in primary tumor samples, in which we observed that the frequency of cells with two chr17 and one TP53 signals was higher in the diffuse-type than in the intestinal-type GC [27]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding corroborates our previous study using dual-color FISH for chr17/ TP53 in primary tumor samples, in which we observed that the frequency of cells with two chr17 and one TP53 signals was higher in the diffuse-type than in the intestinal-type GC [27]. …”
Section: Discussionsupporting
confidence: 92%
“…Although primary tumors of individuals from Northern Brazil present clonal crh17 trisomy or monosomy by FISH analysis [27], chr17 aneusomy is not the most frequent alteration within primary tumors of our population [7, 22, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that the loss of p53 expression leads to the suppression of IGFBP-3 in tumor cells [23]. In our population, we previously described that all gastric samples presented TP53 allelic deletions [24]. Thus, the feedback between p53 and IGFBP-3 may be lost in these samples and other pathways may be inducing IGFBP-3 expression.…”
Section: Discussionmentioning
confidence: 82%
“…We previously observed that only intestinal type gastric cancer samples presented p53 immunoreactivity [24]. Increased immunostaining of p53 can depend on either increased synthesis of wildtype protein or accumulation of mutated protein in the cell [25], which explains the significant difference in IGFBP-3 staining between intestinal (92.3%) and in diffuse type (67.9%).…”
Section: Discussionmentioning
confidence: 96%
“…Previously we also reported the presence of p53 immunoreactivity in all intestinal-type gastric cancer of individuals from Northern Brazil [12]. The p53 immunoreactivity usually depends on the accumulation of mutated p53 proteins in the cell, which leads to a longer half-life [36].…”
Section: Discussionmentioning
confidence: 98%